Revision questions for paediatrics : EMQs with answers explained - Orekunrin, Olamide (Boca Raton : CRC Press, 2019)
This revision tool helps readers strengthen their existing knowledge of childhood disorders through Extended Matching Questions (EMQs) on topics frequently asked in Paediatrics examinations, ranging from neonatology to emergency medicine and public health. Detailed answers in each section build comprehension and knowledge. Many medical schools now examine undergraduates using EMQs, but they also feature highly in postgraduate examinations. This revision aid will therefore also be useful to those preparing for postgraduate examinations such as the Diploma of Child Health (DCH) and Membership of the Royal College of Paediatrics and Child Health (MRCPCH), as well as foundation doctors on their first paediatric rotations and all those wishing to consolidate their knowledge and understanding of Paediatrics.
Originally published: 2010.
Includes index.
Preface, About the authors, List of contributors, Chapter 1 Neonatology, Chapter 2 Neurology and development, Chapter 3 Immunology and infectious disease, Chapter 4 Gastroenterology and endocrinology, Chapter 5 Cardiology and respiratory disease, Chapter 6 Orthopaedics and rheumatology, Chapter 7 Haematology and oncology, Chapter 8 Nephrology and urology, Chapter 9 Emergency paediatrics and non-accidental injury, Chapter 10 Public health and statistics, Index
OCLC-licensed vendor bibliographic record.
Keywords: Pediatrics -- Examinations, questions, etc; MEDICAL / General